Roles of Dietary Cobalt and Administration of Mixed Rumen Bacteria in Regulating Hematological Parameters of Pre-weaning Twin Lambs - T Adelina; A Boediono; I G Permana; T R Wiradarya; D Evvyernie; T Toharmat (Faculty of Animal Science, Bogor Agricultural University, 2013)
Cobalt (Co) is required by rumen microorganism for vitamin B12 synthesis. Vitamin B12 is an important cofactor for methionine synthesis and gluconeogenesis. In young ruminants up to 6–8 wk old, the rumen has not been completely developed and rumen microorganisms are not ready to supply vitamin B12. The aim of this research was to determine the potency of mixed rumen bacteria and dietary supplementation of Co and its effect on plasma glucose, blood minerals (Co, Fe, and Zn) concentrations, and hematology of pre-weaning twin lambs. Twelve one month-old local twin lambs were assigned to 4 groups in a randomized complete block design. Lambs were fed cow milk at 10% body weight, adjusted weekly for 80 d. Mixed rumen bacteria were offered at 15 mL/d (8.295x1010 cfu). Dietary treatments were: 1) basal diet (Control), 2) basal diet + 1 mg/kg DM cyanocobalamin (VitB12) and 3) basal diet + 1 mg/kg DM of Co + administration of 15 mL mixed rumen bacteria (CoBac). There were no treatment effects on neither plasma glucose and blood mineral concentrations nor hematological profiles. This study demonstrated that pre-weaning twin lambs are not responsive to supplementation of Co and administration of mixed rumen bacteria.